Aplikasi Perekrutan dan Penilaian Karyawan Berbasis Web pada PT. XYZ - Ririn Ikana Desanti; Carolyn Feiby Supit; Andree E. Widjaja (ULTIMA InfoSys, 2017)
In a company, the process of employees recruitment and performance appraisal are very crucial. The recruitment is the first process which selects the potential employees that would meet the company’s pre-defined criteria. Meanwhile, the performance appraisal is a way to evaluate employees’ performances whether or not the employees have achieved the company’s goals. In PT. XYZ, both employee recruitment and performance appraisal processes were manually conducted. This manual process were indeed proned to many mistakes and unfair decisions. For that reason, an information system is indispensable to support the aforementioned processes. In this study, we have developed a web-based application which can support the recruitment and performance appraisal process. UML diagram version 2.4 and Rapid Application Development (RAD) with prototyping method were employed to support the development of our application. Analytic Hierarchy Process (AHP) method were also embedded in our application to select and rank the applicants based on several criteria in a more objective manner. The result of this study is a fully functional web-based application which is able to support, automate, as well as accelerate the recruitment and performance appraisal process at PT. XYZ. Index Terms—Recruitment, Performance Appraisal, Web-based Application, Analytical Hierarchy Process